THE IMPACT OF DIGITAL TRANSFORMATION OF MSMEs ON REGIONAL ECONOMIC GROWTH: ANALYSIS OF BPS ECONOMIC CENSUS DATA - Nursiah (Yayasan Amanah Nur Aman, 2025)
This study aims to analyze the impact of MSME digital transformation on regional economic growth using secondary data from the Central Statistics Agency (BPS) for the 2018–2023 period in five provinces in Indonesia. Digital transformation is measured through a digitalization index that includes the use of online platforms and social media, while regional economic growth is proxied by the growth rate of Regional Gross Domestic Product (RGDP), the contribution of MSMEs to RGDP, and employment. The analysis method used was panel data regression with the Ordinary Least Squares (OLS) approach and robust standard error to test the effect of digitalization variables on economic growth. The results showed that increased MSME digitalization had a significant and positive effect on regional GRDP growth, which was reinforced by the contribution of MSMEs to GRDP and employment. These findings imply that MSME digitalization plays a strategic role in strengthening regional competitiveness, creating jobs, and improving local economic resilience. Therefore, the government and stakeholders need to expand policy support, strengthen digital literacy, and build more inclusive technological infrastructure to accelerate the digital transformation of MSMEs throughout Indonesia.